Craig's Quest of the Historical Adam - Gouw, Arvin (Veritas : Jurnal Teologi dan Pelayanan, 2021)
William Lane Craig has written an impressive apologetic book on the topic of the historical Adam. This book is comprehensive and thought-provoking. The theological, scientific, and philosophical argumentations presented in this book are enormous. Theologically, Craig from the very beginning has some fundamental commitments that he wants to defend. He is frank in acknowledging that it is impossible to start from a neutral ground, and I concur. But his theological commitments set him on a quest in approaching the topic by finding evidence for the plausibility of a historical Adam. Scientifically, a skeptical scientist would be very concerned about Craig’s ability to avoid confirmation bias as he evaluates various data to support his arguments, given his theological commitments. Philosophically, since this work is an apologetic exercise to create a case of plausibility for a historical Adam rather than an attempt to prove the existence of the historical Adam, readers may find this either very rewarding or terribly disappointing. Though the case of plausibility is important, it will not convince anybody who does not already believe in the historical Adam. Overall, as a work in theology and science, Craig demonstrates what needs to be done as a ground-clearing exercise before constructing a systematic theology that engages both the scriptures and science. I encourage theologians who want to be Biblically and scientifically relevant to take up the quest as Craig did in this work, knowing well the challenges that lie ahead.